‘The utter disgrace of Jerry-building. On the laborious appreciation of late nineteenth-century housing architecture (Bulletin KNOB, 2012)
At the end of the nineteenth century the term revolutiebouw (jerry-building) had become generally accepted for anything that was not sound. Revolutiebouw – quick, cheap and insolid housebuilding – started more or less simultaneously in the rapidly growing Dutch cities. The phenomenon was widely spread, and just as widely accepted was the emotionally charged term revolutiebouw to characterize complete nineteenth-century districts. Well-known examples are the Hague Schilderswijk, Oude Westen and Oude Noorden in Rotterdam and the Amsterdam Kinker district and De Pijp. Revolutiebouw, for that matter, was an international phenomenon; for instance, Germany had its Schwindelbau and England ‘jerry-building’. In this article, focused on Amsterdam, the central question is what this revolutiebouw actually implies and to what extent this characterization does justice to the rather simple, commonplace nineteenth-century architecture. The research into the origin of the concept on the basis of contemporary sources leads to the conclusion that this was a new, special form of the traditional speculation building. The proverbial ‘revolution’ consists in the financing of the entire building process by mortgage banks and land speculators who – often at their own initiative – brought money, land, materials and builder together. For the rest it is just a matter of speculation building for an unknown market, but on an unprecedentedly large scale. The article outlines that speculation building and owner-occupier building had been undisputed ways of earning money, and hence income, for centuries. Building ‘for the market’ is of all time and formed the driving spirit behind house building in the late nineteenth century, too.The nineteenth-century ring of new districts around the old city was laid out on the basis of the Expansion Plan of ir. J. Kalff (1875-1876). The design was pragmatic in its layout: it took the existing parcelization and property relations into account, and parts of it were regularly adjusted to the wishes of private developers and builders. It is characteristic of the owner-occupier builders during the last four decades of the nineteenth century that they edged their way through the city as it were, with some money of their own or in partnership, to build separate houses or small rows of houses here and there for various target groups. Thus the city grew at a great pace, bit by bit. On the basis of some examples the article outlines the diversity of speculation building in urban development districts.There was enormous resistance against the new, nineteenth-century city. Contemporaries abhorred the decline of the splendid art of architecture: they saw dull façades, poor plans, mechanized components and constructional incompetence. Building economists described an organization method in which costs were minimized and the financial risk was passed on to the craftsman. Urban planners denounced building lines, street widths and building heights. Housing reformers especially noticed alcoves, built-in stairwells and too narrow, deep premises. Thus all speculation building was referred to as revolutiebouw in the reference books, without taking into account the housing demand which it provided for and without noticing any architectonic and urban-planning qualities. It was not until the seventies of the twentieth century, when large parts of the nineteenth-century districts were demolished, that one became aware of the fact that the owner-occupier builders from the second half of the nineteenth century had left us an ample stock of payable, charming houses in attractive surroundings.